Effects of distillers dried grains with solubles and added fat fed immediately before slaughter on growth performance and carcass characteristics of finishing pigs - Coble, K. F.; DeRouchey, Joel M.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; Woodworth, Jason C. (My University, 2017)
The addition of dietary fat has been shown to increase HCW and carcass yield in pigs fed low-fiber corn-soy diets; however, data on added fat in high-fiber, low-energy diets is less available. Therefore, the potential for dietary fat to ameliorate the negative effect high-fiber diets have on carcass yield during the last 3 wk before slaughter is of high importance. This experiment was conducted to determine the interactive effects of 30% distillers dried grains with solubles (DDGS) and 5% added fat fed before slaughter on growth performance and carcass characteristics. A total of 1,258 pigs in 2 groups (initially 105.8 +/- 0.1 kg BW; group 1 PIC 337 x 1,050; group 2 PIC 327 x 1,050) were used in a 20-d experiment. All pigs were fed a common diet with 30% DDGS until 20 d before slaughter. Then, all pens were weighed and allotted to treatments with 20 replicate pens per treatment. Dietary treatments were arranged in a 2 x 2 factorial with 2 diet types (corn-soybean meal-based with or without 30% DDGS) and added fat (0 or 5%; group 1 = tallow; group 2 = choice white grease). Diets were formulated to a constant standardized ileal digestible Lys: NE ratio. There were no treatment x group interactions for any response criteria. Thus, data for the 2 groups were combined for analysis. Overall, there was a tendency for a diet type x added fat interaction for ADG (P = 0.054), whereas this was significant for G: F (P = 0.008). This was a result of 5% added fat increasing ADG and G: F to a greater magnitude for pigs fed the diet containing 30% DDGS (8.6 and 10.4%, respectively) than for pigs fed the corn-soy diet (2.0 and 2.9%, respectively). Although diet type did not affect final live BW, pigs fed the diet containing DDGS had decreased HCW and carcass yield (P < 0.05). Adding 5% fat did not affect carcass yield. In conclusion, adding 5% fat to finishing pig diets containing 30% DDGS approximately 20 d before slaughter improved ADG and G: F but did not overcome the reduction in carcass yield from feeding DDGS.
Citation: Coble, K. F., DeRouchey, J. M., Tokach, M. D., Dritz, S. S., Goodband, R. D., & Woodworth, J. C. (2017). Effects of distillers dried grains with solubles and added fat fed immediately before slaughter on growth performance and carcass characteristics of finishing pigs. Journal of Animal Science, 95(1), 270-278. doi:10.2527/jas2016.0679
Keywords: Fat; Fiber; Finishing Pigs; Withdrawal; Yield; Choice White Grease